Mengupas Kebutuhan Penyuluh Pajak Daerah: Eksplorasi Di Pemerintah Provinsi DKI Jakarta - Wulandari Kartika Sari; Setyowati, Milla Sepliana; Abrar Bilisanimar; Yasmina Prasetyanti Putri (LPPM POLITEKNIK LP3I BANDUNG, 2024)
Local tax revenues in DKI Jakarta Province have not reached their optimal achievement. One of the causes is the low compliance of local taxpayers due to a lack of tax knowledge. Tax administration can improve voluntary tax compliance by providing services and good communication with taxpayers. This role can be carried out through a tax counseling program. This study aims to provide urgency for the functional position of local tax counselors in supporting the resilience of local tax revenues. The research used a qualitative approach with data collection techniques through in-depth interviews, focus group discussions, and literature studies. The study results show that local tax counseling in DKI Jakarta faces obstacles due to a lack of human resources and budget. The absence of a position for tax counselors, currently only limited to task force units, limits the legitimacy of tax counselor authority in carrying out their primary duties and functions. The status of the task force unit has resulted in tax counselors being unable to focus on handling tax counseling in DKI Jakarta because they still have to carry out other administrative duties. Meanwhile, tax counselor officers have a heavy task because they have to master all regulations related to local taxes and the dynamics of its changes and should be able to solve various problems faced by Local Taxpayers. Transferring the tax counselor from the task force unit to a functional position will increase the local tax counselor officers' competence, motivation, and skills to support optimal provincial tax revenues.